Blueprints in obstetrics and gynecology - Callahan, Tamara L. (Blackwell Science, 2001)
Blueprints in Obstetrics and Gynecology presents the principles of Obstetrics and Gynecology in a succinct format that complements the USMLE Step 2 exam. It can be used as a stand-alone text for the Ob/Gyn rotation, or as a review for the USMLE Step 2 and 3 exams. This bestseller includes 125 clinical vignette style questions.